Science and Suffering: Genetics and the Lived Experience of Illness. (9th February 2017) - Halpin, Michael
Abstract: With more than 10, 000 conditions connected to pathological genes, genetic science has the potential to impact illness experience substantively. Building on medical sociological and science studies literatures, my study analyzes how genetic discourses and technologies shape the lived-experience of Huntington Disease (HD). Analysis draws on in-depth interviews conducted in Canada with 24 individuals with the HD mutation and 14 caregivers (e.g., spouses). Study findings detail how genetic discourses and illness experiences intersect to produce "genetic suffering, " a participant-derived concept describing a novel modality of suffering. Genetic suffering is detailed in relation to four themes: 1) Guilt, responsibility, and genetic inheritance, 2) Chance, uncertainty and genetic testing, 3) Ambiguity and genetic onset, and 4) Fatalism and genetic prognosis. After describing the intersections between the science of genetics and suffering in HD families, I discuss the implications of study findings for debates on genetic responsibility and consider the unintended consequences of genetic technologies.